Observation of Wγγ triboson production in proton-proton collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; et al. (Physics letters, 2024)
This letter reports the observation of W(ℓν)γγ production in proton-proton collisions. This measurement uses the full Run 2 sample of events recorded at a center-of-mass energy of s=13 TeV by the ATLAS detector at the LHC, corresponding to an integrated luminosity of 140 fb−1. Events with a leptonically-decaying W boson and at least two photons are considered. The background-only hypothesis is rejected with an observed and expected significance of 5.6 standard deviations. The inclusive fiducial production cross section of W(eν)γγ and W(μν)γγ events is measured to be σfid=13.8±1.1(stat)+2.1−2.0(syst)±0.1(lumi) fb, in agreement with the Standard Model prediction.
Online verfügbar: 14. Dezember 2023, Artikelversion: 20. Dezember 2023
*The ATLAS Collaboration: G. Aad, L.M. Baltes, F. Bartels, M.M. Czurylo, F. Del Rio, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und 2909 weitere Personen]
Im Titel steht der Buchstabe "s" unter dem Wurzelsymbol
Gesehen am 17.09.2024